Extension Agency Contact and Technology Sharing among Trainee and Non-trainee Layer Farmers - Kumari, Maina; Sagar, M.P.; Dhawal, Kamlesh Kumar; Bhumra, Harshita (Indian Journal of Extension Education, 2019)
The study was conducted to assess the extent of extension agency contact and technology sharing among layer farmers. For investigation equal (54) numbers of trainee and non-trainee layer farmers were selected from five different agro-climatic zones (out of nine) of state UP. Thus, total sample size was 108. These were measured by data collected through mailed questionnaire and telephonic survey. The study revealed that for trainee layer farmers, CARI (Central Avian Research Institute) was first choice and frequently contacted extension agency followed by Venkys and SDAH (State Animal Husbandry Department). While, for non-trainee layer farmers, SDAH was contacted more oftenly, followed by KVKs and Venkys. In case of technical sharing, about 72.23 per cent of trainee layer farmers had low level (14 farmers) level of technology sharing. While, in case of non-trainees, huge majority (85.18%) of layer farmers were belonging to low level, followed by medium (9.26%) and high (5.56%) level of technology sharing among farmers. The average technology shared among farmers of the trainee and non-trainee layer farmers were 5.27 and 5.17, respectively. Technology sharing was higher in trainee layer farmers. This might be due to their high knowledge and adoption level, high socio-economic status due to training which makes them early adopters.
Keywords: Adoption; Extension agency; Knowledge; Layer farmers; Technology